2021
DOI: 10.4269/ajtmh.20-1168
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the Point-of-Care Urine Strip Test for Schistosoma Circulating Cathodic Antigen (POC-CCA) Tested in Non-Endemic Pregnant Women and Young Children

Abstract: The point-of-care urine based strip test for the detection of circulating cathodic antigen (POC-CCA) in schistosome infections is a frequently used tool for diagnosis and mapping of Schistosoma mansoni in school-aged children. Because of its ease of use, the test is increasingly applied to adults and preschool-aged children (PSAC), but its performance has not been specifically evaluated in these target groups. Recent observations have raised concerns about possible reduced specificity, in particular in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…29 POC-CCA traces were considered negative for the analysis. 31 Data were entered into a Microsoft Excel spreadsheet (Microsoft Corp., Redmond, WA) and analyzed using Graph-Pad Prism 8.4.2 (GraphPad Software Inc., San Diego, CA) and SPSS version 25 (IBM Corp., Armonk, NY). Statistical analysis was performed using descriptive statistics.…”
Section: Methodsmentioning
confidence: 99%
“…29 POC-CCA traces were considered negative for the analysis. 31 Data were entered into a Microsoft Excel spreadsheet (Microsoft Corp., Redmond, WA) and analyzed using Graph-Pad Prism 8.4.2 (GraphPad Software Inc., San Diego, CA) and SPSS version 25 (IBM Corp., Armonk, NY). Statistical analysis was performed using descriptive statistics.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, depending on the diagnostic method used, the measures of drug efficacy (ERR and CR) can differ significantly. However, there are concerns surrounds false positive results from the POC-CCA (169,170). Further explanations for a negative KK result and positive POC-CCA result include the presence of single sex infections either acquired or the result of drug treatment could explain the disruption of egg production despite an active infection (171)(172)(173)(174).…”
Section: Antigen Detectionmentioning
confidence: 99%
“…Our study also found that there were no differences in POC-CCA specificity in small ruminants across sites and parasite species, and that POC-CCA specificity was not affected by haematuria. This contrasts with results in humans, where POC-CCA specificity has been found to be affected by the host’s age (in pre-school aged children < 5 years), their pregnancy status, and whether or not they have haematuria or a urogenital infection [40, 59].…”
Section: Discussionmentioning
confidence: 67%